Pengaruh Net Profit Margin, Return On Assets, Debt To Equity Ratio Dan Ito Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Maya Sabirina Panggabean; Angelica Angelica; Dinny Khairunnisa Aprilia; Edyson Wijaya; Sonia Febriani (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The increase in profit obtained by a company within a certain period is the definition of profit growth. The percentage increase in profit can indicate the company's financial position. The purpose of this research is to know how Net Profit Margin, DER, ROA and ITO can impact on profit growth in the company. The type of research used is descriptive quantitative using secondary data, the sample is determined using the purposive sampling method, and the examination method uses multiple linear regression analysis.The population of the company is 139 manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2019. Based on the research results, it is known that NPM has an effect of 34.38 percent, ROA has an effect of -45.71 percent, DER has an effect of 49.2 percent and ITO has an effect of 0.5 percent on Profit Growth. Simultaneously, NPM, DER, ROA and ITO have a positive and relevant impact. Partially, only NPM and DER have a positive and relevant effect on Profit Growth, while ROA and ITO have no relevant impact on Profit Growth. Keywords: Net Profit Margin, Return On Assets, Debt to Equity Ratio and ITO